The Role of Public Services in Improving Community Welfare and Reducing Stunting in East Lombok - Sadimin Sadimin; Herlina Mutiara; Ignatius Wahyu Anggono; Evi Satispi; Endang Sulastri (Riwayat: Educational Journal of History and Humanities, 2025)
Public service plays a crucial role in improving community welfare and addressing public health challenges, including stunting, particularly in developing regions such as East Lombok, Indonesia. This study aims to explore the contribution of public services in enhancing social well-being and reducing stunting rates through qualitative methods, specifically literature review and library research. By analyzing existing studies, government policies, and empirical reports, this research identifies key public service initiatives, including healthcare programs, nutritional support, education, and sanitation improvements, that directly impact community welfare and child growth. The findings indicate that effective public services, supported by strong governmental commitment and community participation, significantly contribute to reducing stunting prevalence. Furthermore, access to quality healthcare, maternal education, and social protection programs are essential in fostering sustainable development and improving overall public health. The study also highlights challenges such as inadequate infrastructure, limited funding, and bureaucratic inefficiencies that hinder optimal service delivery. Therefore, enhancing governance, increasing public awareness, and strengthening policy implementation are crucial to ensuring long-term success in stunting prevention and community welfare improvement. This research contributes to the existing literature by emphasizing the importance of integrated public services in achieving health and development goals. Future studies should focus on field-based evaluations and comparative analyses to further assess the effectiveness of public service interventions in various socio-economic contexts.